1998
DOI: 10.1111/j.1442-9071.1998.tb01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the amoebicidal efficacy of contact lens disinfection systems

Abstract: Multipurpose systems have variable anti-amoeba activity and storage cases contaminated by bacteria may enhance amoeba survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…23 The studies concluded that H 2 O 2 was most effective at the shortest storage times against Acanthamoeba, while PQ-1 and PHMB were determined to be completely ineffective. 21,23,51 BAK and chlorhexidine-thimerosal were sufficient at killing both trophozoites and cysts depending on exposure time 21,23 but, as previously noted, these preservatives are no longer used in commercially available MPS due to toxicity.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…23 The studies concluded that H 2 O 2 was most effective at the shortest storage times against Acanthamoeba, while PQ-1 and PHMB were determined to be completely ineffective. 21,23,51 BAK and chlorhexidine-thimerosal were sufficient at killing both trophozoites and cysts depending on exposure time 21,23 but, as previously noted, these preservatives are no longer used in commercially available MPS due to toxicity.…”
mentioning
confidence: 84%
“…Studies have confirmed that PHMB solutions are completely ineffective against Acanthamoeba (five MPS tested with some overlap of MPS formulas in the studies). 10,[21][22][23]47,[51][52][53][54] While bacteria are much more common causative agents of MK, fungal or amoebal infections can quickly become sight-threatening and must also be considered.…”
Section: Modern High Molecular Weight Preservativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Propyl‐betaine is a mild surfactant found in cosmetic formulations for skin, hair cleansing and conditioning . Polyhexanide has been used as a disinfectant in swimming pools to control contamination with various amoeboid and bacterial organisms, including Pseudomonas aeruginosa . Additionally, it is commonly found in no‐rinse products for cleansing contact lenses, including products marketed for use with ‘sensitive‐eyes’ .…”
Section: Introductionmentioning
confidence: 99%
“…Stapleton et al 31 and Hughes et al 32 indicated that the higher efficacy of peroxide solutions is expected in the absence of neutralisation, as was the case in this study, which therefore must be interpreted with caution as neutralisation is an essential step when using peroxide disinfection systems. This is particularly so as with the one-step peroxide system, the neutralising platinum disc is introduced during the disinfection process and therefore may not show the same efficacy as found in this study.…”
Section: Average No Of Cfus Remainingmentioning
confidence: 50%